A bench-top Dark-Root device built with LEGO® bricks enables a non-invasive plant root development analysis in soil conditions mirroring nature - Dermendjiev, Georgi; Schnurer, Madeleine; Stewart, Ethan; Nägele, Thomas; Marino, Giada; Leister, Dario; Thür, Alexandra; Plott, Stefan; Jeż, Jakub; Ibl, Verena (Frontiers in Plant Science, 2023)
Roots are the hidden parts of plants, anchoring their above ground counterparts in the soil. They are responsible for water and nutrient uptake, as well as for interacting with biotic and abiotic factors in the soil. The root system architecture (RSA) and its plasticity are crucial for resource acquisition and consequently correlate with plant performance, while being highly dependent on the surrounding environment, such as soil properties and therefore environmental conditions. Thus, especially for crop plants and regarding agricultural challenges, it is essential to perform molecular and phenotypic analyses of the root system under conditions as near as possible to nature (#asnearaspossibletonature). To prevent root illumination during experimental procedures, which would heavily affect root development, Dark-Root (D-Root) devices (DRDs) have been developed. In this article, we describe the construction and different applications of a sustainable, affordable, flexible, and easy to assemble open-hardware bench-top LEGO® DRD, the DRD-BIBLOX (Brick Black Box). The DRD-BIBLOX consists of one or more 3D-printed rhizoboxes which can be filled with soil, while still providing root visibility. The rhizoboxes sit in a scaffold of secondhand LEGO® bricks, which allows root development in the dark as well as non-invasive root-tracking with an infrared (IR) camera and an IR light emitting diode (LED) cluster. Proteomic analyses confirmed significant effects of root illumination on barley root and shoot proteomes. Additionally, we confirmed the significant effect of root illumination on barley root and shoot phenotypes. Our data therefore reinforces the importance of the application of field conditions in the lab and the value of our novel device, the DRD-BIBLOX. We further provide a DRD-BIBLOX application spectrum, spanning from investigating a variety of plant species and soil conditions as well as simulating different environmental conditions and stresses, to proteomic and phenotypic analyses, including early root tracking in the dark.